Aspectos conceptuales de la enseñanza de la psiquiatría en Colombia (2012)
Introduction: The teaching of Psychiatry in Colombia is the result of the accumulation of different conceptual streams dating back to early twentieth century and the beginning of Psychiatric study. By a way of different teaching methods, this knowledge was transferred from generation to generation to materialize into its current formation. Methods: Different key moments are recognied in the history of Psychiatry throughout the world and the introduction of these trends in Colombia, and sepcifically its impacto n teaching. Results: The current structure derives from French elemens of organ-dynamic Psychiatry, both conceptual and clinical, likewise, it is formed from conception kraepeliana and biologic therapies introduced from the second quarter of the last century and the psychoanalytic trend introduced since 1950. Conclusion: The Psychiatric Departments of Colombia form prominently in Pychiatry and are skillful in managing mental illness, with basic knowledge of pathophysiology and psychopathology, as well as good training in psychopharmacology and psychotherap